Highly efficient and selective H2/CH4 separation by graphene membranes with embedded crown ethers. (12th July 2022) - Gu, Zonglin; Shi, Zipeng; Lin, Guojun; Zeng, Shuming; Elmegreen, Bruce; Luan, Binquan
Abstract: Designing a highly selective and fast separation membrane is critical to realize H2 -sieving with efficient performance, which is still a challenge by far. In this study, we combine molecular dynamics (MD) and first-principle approaches to investigate the H2 separation property of graphene crown ether. Our MD results demonstrate that graphene crown ether exhibits a superior H2 -sieving performance under various temperatures and external pressures, allowing fast passage for H2 while completely rejecting CH4 . The H2 permeability exceeds 10 5 GPU at selectivities exceeding 1500. These results highlight an outstanding performance of crown ether pores for separating H2 from mixtures with CH4 . Observed from MD simulation trajectories, this highly selective separation is caused by the intrinsic dimensional difference between the two types of gases and the pore. The first-principle calculations further confirm that it is energetically more favorable for H2 to transit the graphene crown ether than for CH4 . Our findings suggest a novel application of the graphene crown ether in H2 -sieving with great promise for future membrane designs. Highlights: H2 /CH4 separation by graphene membranes embedded with crown ether. Graphene crown ether nanopores realize the highly efficient and selective sieving of H2 from mixture of CH4 . Graphene crown ether achieves the pure H2 gas after sieving. Exploration from molecular level by using molecular dynamics simulation and first-principle approaches.